2021
DOI: 10.1155/2021/6256618
|View full text |Cite|
|
Sign up to set email alerts
|

[Retracted] Theaflavin Chemistry and Its Health Benefits

Abstract: Huge epidemiological and clinical studies have confirmed that black tea is a rich source of health-promoting ingredients, such as catechins and theaflavins (TFs). Furthermore, TF derivatives mainly include theaflavin (TF1), theaflavin-3-gallate (TF2A), theaflavin-3 ′ -gallate (TF2B), and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
40
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(42 citation statements)
references
References 146 publications
2
40
0
Order By: Relevance
“…There are structural similarities and differences among the four components of theaflavin. 45 A preliminary assessment of the role of the four theaflavin fractions in modulating inflammatory responses in a model of inflammatory resistance in this study revealed that the different fractions of theaflavin monomers all exhibited some inhibition of LPS-induced myotubular inflammatory factors but with some variability among the fractions (Figure 8). Some studies have reported that theaflavin mixtures inhibit inflammation in rat tissues, 46 which is also consistent with our study.…”
Section: ■ Discussionmentioning
confidence: 75%
“…There are structural similarities and differences among the four components of theaflavin. 45 A preliminary assessment of the role of the four theaflavin fractions in modulating inflammatory responses in a model of inflammatory resistance in this study revealed that the different fractions of theaflavin monomers all exhibited some inhibition of LPS-induced myotubular inflammatory factors but with some variability among the fractions (Figure 8). Some studies have reported that theaflavin mixtures inhibit inflammation in rat tissues, 46 which is also consistent with our study.…”
Section: ■ Discussionmentioning
confidence: 75%
“…TF3 is a large and copious component of black tea, generated by the chemical reaction of epigallocatechin gallate (EGCG) and epicatechin gallate (ECG) during fermentation 94 . As a result, TF3 has been discovered to have diverse pharmacological properties, together with anti-inflammatory and free radicals or ROS scavenging abilities 73,95 . According to a new study, women who drink a lot of black tea have a lower risk of ageing 96 .…”
Section: Antioxidant Effectmentioning
confidence: 99%
“…Additionally, oolonghomobisflavan-A and theasinensin-D are poorly soluble in water 32 , while theaflavin and its derivatives are highly soluble 33 . Considering the above-stated reasons and the enormous therapeutic potential of theaflavin 3-gallate 34 , 35 , we performed wet-lab studies to test the inhibition potential of theaflavin 3-gallate along with GC376 (known inhibitors of M pro ) and theaflavin (precursor for theaflavin 3-gallate) against M pro protein of SARS-CoV-2. The cell-based assay was performed to confirm the antiviral activity of theaflavin 3-gallate.…”
Section: Introductionmentioning
confidence: 99%